PENGARUH VOLUNTARY DISCLOSURE, RELEVANSI NILAI, DAN KEPEMILIKAN ASING TERHADAP COST OF EQUITY: ASIMETRI INFORMASI SEBAGAI VARIABEL PEMEDIASI - Clara Alverina Santoso; Fransiskus E. Daromes (Faculty of Economic and Business Universitas STIKUBANK, 2019)
The purpose of this study was to investigate the effect of voluntary disclosure, value relevance, and foreign ownership on information asymmetry, the effect of voluntary disclosure, value relevance, foreign ownership, and information asymmetry on the cost of equity and the mediating role of information asymmetry to voluntary disclosure, value relevance, and foreign ownership of the cost of equity. Population used in this study is the whole manufacturing company listed on Indonesia Stock Exchange (IDX) period 2015 - 2017. Total samples are 240 companies for 3 years selected by purposive sampling method and using secondary data, i.e. annual report and financial report collected from IDX database, yahoo finance and each company’s official website. The results of this study indicate that voluntary disclosure and value relevance of financial statements can reduce information asymmetry, while foreign ownership can increase information asymmetry, but the influence of value relevance and foreign ownership is weak. The findings also indicate voluntary disclosure, value relevance, and information asymmetry can increase the cost of equity, while foreign ownership can reduce the cost of equity, but the effect of voluntary disclosure, value relevance, and foreign ownership is weak. This finding implies that companies must pay attention to the problem of information asymmetry because investor trust is important in reducing the company's cost of equity. Low information asymmetry will also increase security for investors in investing. Keywords: voluntary disclosure, value relevance, foreign ownership, asymmetry information, and cost of equity.